Electrostatic image developer, process cartridge, image forming device, and image forming method
By using electrostatic image developer of layered structural compound particles containing nitrogen atoms and magnetic particles, combined with the technique of controlling the surface roughness of the resin-coated carrier, the problems of high-temperature and high-humidity download body adhesion and ink thirst under low temperature and low humidity are solved, and more stable image formation is achieved.
Patent Information
- Application Number
- CN202010777010.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2020-08-05
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-08-05
AI Technical Summary
The existing electrostatic image developer is prone to carrier adhesion in high temperature and high humidity environments, and may lead to ink thirst in low temperature and low humidity environments.
An electrostatic image developer containing toner particles, layered structural compound particles containing nitrogen atoms, and a resin-coated carrier having magnetic particles and a coated resin layer are used. The maximum height Ry of the surface roughness curve of the resin-coated carrier of the developer is controlled to be 0.01 μm or more than 0.20 μm to suppress the adhesion of carrier and the occurrence of ink thirst.
It effectively suppresses the attachment of carrier when low-density images are formed in high-temperature and high-humidity environments, and prevents ink thirst of high-density images in low-temperature and low-humidity environments, thereby improving the stability and quality of image formation.
Smart Images

Figure BDA0002618806110000261 
Figure BDA0002618806110000291 
Figure HDA0002618806120000011
Abstract
Description
Technical Field
[0001] The present invention relates to an electrostatic image developer, a process cartridge, an image forming apparatus and an image forming method. Background Art
[0002] Japanese Patent Application Laid-Open No. 2006-317489 discloses a toner in which 0.1 to 2.0 parts by weight of melamine cyanurate powder having a volume average particle size of 3 to 9 μm is added to a base toner having an average circularity of 0.94 to 0.995 and a volume average particle size of 3 to 9 μm based on 100 parts by weight of the base toner.
[0003] Japanese Patent Application Laid-Open No. 2009-237274 discloses a positively chargeable toner, wherein 0.01 to 0.5 parts by weight of melamine cyanurate particles having a number average primary particle size of 0.05 μm to 1.5 μm are added to colored resin particles containing a binder resin, a colorant, and a positive charge control agent, relative to 100 parts by weight of the colored resin particles. Summary of the invention
[0004] Technical problem to be solved by the invention
[0005] The technical problem to be solved by the present invention is to provide an electrostatic image developer. Compared with an electrostatic image developer comprising toner particles and a resin-coated carrier but not containing layered structure compound particles containing nitrogen atoms or an electrostatic image developer in which the maximum height Ry of the surface roughness curve of the resin-coated carrier is greater than 0.20 μm, the electrostatic image developer of the present invention can inhibit the occurrence of beads carry over when continuously forming low-density images in a high-temperature and high-humidity environment (temperature 30°C and relative humidity 88%), and can inhibit the occurrence of ink starvation when continuously forming high-density images in a low-temperature and low-humidity environment (temperature 10°C and relative humidity 15%).
[0006] Means for solving technical problems
[0007] According to the first embodiment of the present invention, there is provided an electrostatic image developer comprising toner particles, layered structure compound particles containing nitrogen atoms, and a resin-coated carrier having magnetic particles and a resin layer coating the magnetic particles, wherein the surface of the resin-coated carrier has a maximum height Ry of a roughness curve of not less than 0.01 μm and not more than 0.20 μm as specified in JIS B0601:1994.
[0008] According to the second aspect of the present invention, the surface of the resin-coated carrier has a maximum height Ry of a roughness curve specified in JIS B0601:1994 of 0.01 μm or more and 0.10 μm or less.
[0009] According to a third aspect of the present invention, the volume average particle size of the layered structure compound particles is 0.1 μm or more and 20 μm or less.
[0010] According to a fourth aspect of the present invention, the volume average particle size of the layered structure compound particles is 0.3 μm or more and 10 μm or less.
[0011] According to a fifth aspect of the present invention, the content of the layered structure compound particles is not less than 0.01 parts by mass and not more than 0.50 parts by mass based on 100 parts by mass of the toner particles.
[0012] According to a sixth aspect of the present invention, the content of the layered structure compound particles is not less than 0.01 parts by mass and not more than 0.30 parts by mass based on 100 parts by mass of the toner particles.
[0013] According to a seventh aspect of the present invention, the layered structure compound particles include at least one selected from the group consisting of melamine cyanurate particles and boron nitride particles.
[0014] According to the 8th aspect of the present invention, there is provided a processing box which is loaded and unloaded in an image forming apparatus and has a developing mechanism which stores the electrostatic image developer and develops the electrostatic image formed on the surface of the image holding body into a toner image using the electrostatic image developer.
[0015] According to a ninth aspect of the present invention, there is provided an image forming apparatus comprising:
[0016] Image holding body;
[0017] A charging mechanism for charging the surface of the image holding body;
[0018] An electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holding member;
[0019] A developing mechanism storing the electrostatic image developer and developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer;
[0020] a transfer mechanism for transferring the toner image formed on the surface of the image holding member to the surface of a recording medium; and
[0021] The fixing mechanism fixes the toner image transferred to the surface of the recording medium.
[0022] According to a tenth aspect of the present invention, there is provided an image forming method comprising:
[0023] Charging, charging the surface of the image holding body;
[0024] Electrostatic image formation, forming an electrostatic image on the charged surface of the image holding member;
[0025] developing, using the electrostatic image developer to develop the electrostatic image formed on the surface of the image holding member into a toner image;
[0026] Transferring, transferring the toner image formed on the surface of the image holding body to the surface of a recording medium; and
[0027] Fixing: Fixing the toner image transferred to the surface of the recording medium.
[0028] Effects of the Invention
[0029] According to the above-mentioned scheme 1 or 7, an electrostatic image developer is provided. Compared with an electrostatic image developer comprising toner particles and a resin-coated carrier but not containing layered structure compound particles containing nitrogen atoms or an electrostatic image developer in which the maximum height Ry of the surface roughness curve of the resin-coated carrier is greater than 0.20μm, the electrostatic image developer of this scheme can inhibit the occurrence of carrier adhesion (beads carry over) when low-density images are continuously formed under a high-temperature and high-humidity environment, and can inhibit the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0030] According to the above-mentioned second scheme, an electrostatic image developer is provided. Compared with the case where the maximum height Ry of the roughness curve is greater than 0.10μm, the electrostatic image developer of this scheme can suppress the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0031] According to the third scheme, an electrostatic image developer is provided. Compared with the case where the volume average particle size of the layered structure compound particles is less than 0.1 μm or greater than 20 μm, the electrostatic image developer of this scheme can suppress the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0032] According to the fourth scheme, an electrostatic image developer is provided. Compared with the case where the volume average particle size of the layered structure compound particles is less than 0.3 μm or greater than 10 μm, the electrostatic image developer of this scheme can suppress the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0033] According to the fifth embodiment, an electrostatic image developer is provided. Compared with a case where the content of layered structure compound particles is less than 0.01 parts by mass or greater than 0.50 parts by mass relative to 100 parts by mass of toner particles, the electrostatic image developer of this embodiment can suppress the occurrence of carrier adhesion when a low-density image is continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when a high-density image is continuously formed under a low-temperature and low-humidity environment.
[0034] According to the sixth embodiment, an electrostatic image developer is provided. Compared with a case where the content of layered structure compound particles is less than 0.01 parts by mass or greater than 0.30 parts by mass relative to 100 parts by mass of toner particles, the electrostatic image developer of this embodiment can suppress the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0035] According to the above-mentioned eighth scheme, a processing box is provided. Compared with an electrostatic image developer in which the electrostatic image developer comprises toner particles and a resin-coated carrier but does not contain layered structure compound particles containing nitrogen atoms, or an electrostatic image developer in which the maximum height Ry of the surface roughness curve of the resin-coated carrier is greater than 0.20 μm, the electrostatic image developer in this scheme can inhibit the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can inhibit the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0036] According to the above-mentioned ninth scheme, an image forming device is provided. Compared with an electrostatic image developer in which the electrostatic image developer comprises toner particles and a resin-coated carrier but does not contain layered structure compound particles containing nitrogen atoms, or an electrostatic image developer in which the maximum height Ry of the surface roughness curve of the resin-coated carrier is greater than 0.20 μm, the electrostatic image developer in this scheme can inhibit the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can inhibit the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment.
[0037] According to the above-mentioned scheme 10, an image forming method is provided. Compared with an electrostatic image developer in which the electrostatic image developer comprises toner particles and a resin-coated carrier but does not contain layered structure compound particles containing nitrogen atoms, or an electrostatic image developer in which the maximum height Ry of the surface roughness curve of the resin-coated carrier is greater than 0.20 μm, the electrostatic image developer in this scheme can suppress the occurrence of carrier adhesion when low-density images are continuously formed under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation when high-density images are continuously formed under a low-temperature and low-humidity environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1This is a schematic structural diagram showing an example of the image forming apparatus according to the present embodiment.
[0039] Figure 2 This is a schematic structural diagram showing an example of a process cartridge that is attached to and detached from the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION
[0040] The following is a description of embodiments of the present invention. These descriptions and examples are intended to illustrate the embodiments and are not intended to limit the scope of the embodiments.
[0041] In the present invention, the numerical range expressed using "to" means a range including the numerical values described before and after "to" as the minimum value and the maximum value, respectively.
[0042] In the numerical range recorded in stages among the present invention, the upper limit or lower limit recorded in a numerical range can be replaced by the upper limit or lower limit of the numerical range in other stages recorded. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit of this numerical range can be replaced by the value shown in the embodiment.
[0043] The term "step" in the present invention includes not only an independent step but also a step that cannot be clearly distinguished from other steps as long as the intended purpose of the step can be achieved.
[0044] When the embodiments of the present invention are described with reference to the drawings, the configuration of the embodiments is not limited to the configuration shown in the drawings. In addition, the sizes of the components in the drawings are schematic, and the relative relationship between the sizes of the components is not limited to this.
[0045] Each component in the present invention may contain two or more corresponding substances. When referring to the amount of each component in the composition of the present invention, if there are two or more substances corresponding to each component in the composition, unless otherwise stated, it refers to the total amount of the two or more substances present in the composition.
[0046] The particles corresponding to each component in the present invention may include two or more kinds of particles. When two or more kinds of particles corresponding to each component are present in the composition, unless otherwise stated, the particle size of each component refers to the value for the mixture of the two or more kinds of particles present in the composition.
[0047] In the present invention, “toner” means “toner for electrostatic image development”, and “carrier” means “carrier for electrostatic image development”. “Electrostatic image developer” is also referred to as “developer”.
[0048] <Electrostatic Image Developer>
[0049] The developer of this embodiment includes: toner particles, layered structure compound particles containing nitrogen atoms, and a resin-coated carrier having magnetic particles and a resin layer coating the above-mentioned magnetic particles; the surface of the above-mentioned resin-coated carrier has a maximum height Ry of a roughness curve specified by JIS B0601:1994 of not less than 0.01μm and not more than 0.20μm.
[0050] The maximum height Ry of the roughness curve is an index of surface roughness. The maximum height Ry of the surface roughness curve of the resin-coated carrier in the present embodiment is measured as follows in accordance with JIS B0601:1994.
[0051] The surface of the resin-coated carrier is observed at an appropriate magnification (e.g., 1000 times magnification) using a surface shape measuring device (e.g., "Ultra-deep Color 3D Shape Measurement Microscope VK-9700" manufactured by KEYENCE Co., Ltd.), and a roughness curve is obtained with a sampling length value of 0.08 mm. A reference length of 10 μm is extracted from the roughness curve in the direction of its average line, and the distance Ry (μm) between the peak top line and the valley bottom line is calculated. Ry is calculated for each of 2000 resin-coated carriers, and the arithmetic average is taken.
[0052] The developer of this embodiment can suppress the occurrence of beads carry over (a phenomenon in which beads adhere to an electrostatic image on the surface of an image holder) when continuously forming low-density images under a high-temperature and high-humidity environment, and can suppress the occurrence of ink starvation (whitening of image edges) when continuously forming high-density images under a low-temperature and low-humidity environment. The mechanism is presumed to be as follows.
[0053] In a developer in which the toner is charged by stirring and rubbing between the toner and the resin-coated carrier, the resin layer of the resin-coated carrier is continuously worn away by the stirring stress in the developer, and the exposed area of the magnetic particles on the surface of the resin-coated carrier may increase. In this case, the resistance of the resin-coated carrier decreases, and carrier adhesion (beads carryover) may occur. This phenomenon is significant in the continuous formation of low-density images in a high-temperature and high-humidity environment (e.g., temperature 30°C and relative humidity 88%) where the external additives are difficult to be released from the toner particles (i.e., the external additives are difficult to cover the surface of the resin-coated carrier) and the stirring stress in the developer is continued.
[0054] In view of the above phenomenon, it is believed that when the developer contains layered structure compound particles containing nitrogen atoms, the layered structure compound particles cover the exposed portion of the magnetic particles on the surface of the resin-coated carrier, thereby suppressing the occurrence of carrier attachment (beads carry over). It is speculated that the layered structure compound particles containing nitrogen atoms are more easily electrostatically attracted to the exposed portion of the magnetic particles than the resin layer because they contain nitrogen atoms, and the layered structure compound particles (particles of a compound having a layered structure with an interlayer distance of angstroms) attached to the exposed portion of the magnetic particles cover the exposed portion of the magnetic particles.
[0055] On the other hand, if the exposed portion of the magnetic particles on the surface of the resin-coated carrier is excessively covered with materials or material fragments contained in the developer (e.g., various external additives, resin peeled from the toner particles, resin peeled from the resin-coated carrier), the resistance of the resin-coated carrier increases, and ink starvation may occur. This phenomenon is significant in the continuous formation of high-density images in a low-temperature and low-humidity environment (e.g., temperature 10°C and relative humidity 15%) where external additives are easily released from toner particles (i.e., external additives are easily covered on the surface of the resin-coated carrier) and the toner residence time in the developer is short (i.e., triboelectric charging of the toner is easily insufficient).
[0056] In view of the above phenomenon, it is believed that if the maximum height Ry of the roughness curve on the surface of the resin-coated carrier is less than 0.20 μm, the material or material fragments contained in the developer are not easily hooked on the surface of the resin-coated carrier, and the occurrence of ink starvation can be suppressed without excessively covering the exposed portion of the magnetic particles. From this aspect, the maximum height Ry of the roughness curve on the surface of the resin-coated carrier is more preferably less than 0.15 μm, further preferably less than 0.10 μm, and further preferably less than 0.08 μm. Among them, since it is difficult to eliminate the fine concave-convex on the surface of the resin-coated carrier, the maximum height Ry of the roughness curve on the surface of the resin-coated carrier is more than 0.01 μm, and from the perspective of ease of manufacturing, it is more preferably more than 0.04 μm.
[0057] Examples of methods for adjusting the maximum height Ry of the surface roughness curve of the resin-coated carrier include: using magnetic particles with less surface irregularities; making the resin layer relatively thick; and the like.
[0058] As a method for forming a resin layer on the surface of magnetic particles, there are a wet method (a method using a solvent that dissolves or disperses the resin) and a dry method (a method that does not use a solvent that dissolves or disperses the resin). From the perspective of suppressing the maximum height Ry of the surface roughness curve of the resin-coated carrier to a low level, the dry method is preferred. An embodiment of the dry method is described below.
[0059] The resin-coated carrier, layered structure compound particles, and toner particles constituting the developer of this embodiment are described in detail below.
[0060] [Resin coated carrier]
[0061] The resin-coated carrier has magnetic particles and a resin layer coating the magnetic particles.
[0062] -Magnetic particles-
[0063] The magnetic particles are not particularly limited, and known magnetic particles used as core materials of carriers can be applied. Specifically, magnetic particles include particles of magnetic metals such as iron, nickel, and cobalt; particles of magnetic oxides such as ferrite and magnetite; resin-impregnated magnetic particles obtained by impregnating porous magnetic powder with resin; magnetic powder-dispersed resin particles obtained by dispersing and mixing magnetic powder in resin; and the like. As the magnetic particles in this embodiment, ferrite particles are preferred.
[0064] The volume average particle size of the magnetic particles is preferably 10 μm to 100 μm, more preferably 20 μm to 80 μm, and even more preferably 30 μm to 60 μm.
[0065] Regarding the magnetic force of the magnetic particles, the saturation magnetization in a magnetic field of 3000 oersted is preferably 50emu / g or more, more preferably 60emu / g or more. The above saturation magnetization is measured using a vibrating sample type magnetometer VSMP10-15 (manufactured by Dongying Industrial Co., Ltd.). The measurement sample is placed in a cell with an inner diameter of 7mm and a height of 5mm and is set in the above device. During the measurement, an external magnetic field is applied and scanned to a maximum of 3000 oersted. Then the external magnetic field is reduced and a hysteresis curve is drawn on a recording paper. The saturation magnetization, residual magnetization, and holding force are obtained based on the data of the curve.
[0066] The volume resistance (volume resistivity) of the magnetic particles is preferably 1×10 5 Ω·cm or more 1×10 9 Ω·cm or less, more preferably 1×10 7 Ω·cm or more 1×10 9 Ω·cm or less.
[0067] The volume resistivity (Ω·cm) of magnetic particles is measured as follows. The object to be measured is placed flatly on a 20 cm 2 The surface of the circular fixture of the electrode plate is formed into a layer. The above 20 cm 2Electrode plates are used to sandwich the layer. In order to ensure that there is no gap between the object to be measured and the electrode plates, a load of 4 kg is applied to the electrode plates arranged on the layer, and then the thickness of the layer (cm) is measured. The upper and lower electrodes of the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to the two electrodes according to an electric field of 103.8 V / cm, and the current value (A) flowing through at this time is read. The measurement environment is set to a temperature of 20°C and a humidity of 50% RH. The calculation formula for the volume resistivity (Ω·cm) of the object to be measured is shown below.
[0068] R=E×20 / (I-I0) / L
[0069] In the above formula, R represents the volume resistance of the object to be measured (Ω·cm), E represents the applied voltage (V), I represents the current value (A), I0 represents the current value (A) at an applied voltage of 0V, and L represents the thickness of the layer (cm). The coefficient 20 represents the area of the electrode plate (cm 2 ).
[0070] -Resin layer covering magnetic particles-
[0071] The resin constituting the resin layer includes: styrene-acrylic acid copolymer; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resins, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymer; pure silicone resin composed of organic siloxane bonds or its modified products; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyester; polyurethane; polycarbonate; amino resins such as urea-formaldehyde resin; epoxy resin; and the like.
[0072] The resin layer preferably contains an acrylic resin having an alicyclic structure. As the polymerization component of the acrylic resin having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (e.g., an alkyl (meth)acrylic acid ester having an alkyl carbon number of 1 to 9) is preferred, and specifically, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. can be cited. One of these monomers can be used, or two or more of them can be used in combination.
[0073] The acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic structure is preferably 75 mol% to 100 mol%, more preferably 85 mol% to 100 mol%, and further preferably 95 mol% to 100 mol%.
[0074] The proportion of the acrylic resin having an alicyclic structure in the entire resin contained in the resin layer is preferably 80% by mass or more, more preferably 90% by mass or more, and it is further preferred that substantially all the resins are acrylic resins having an alicyclic structure.
[0075] In the resin layer, inorganic particles may be included for the purpose of controlling charging or resistance. Examples of the inorganic particles include carbon black; metals such as gold, silver, and copper; metal compounds such as barium sulfate, aluminum borate, potassium titanate, titanium oxide, zinc oxide, tin oxide, tin oxide doped with antimony, indium oxide doped with tin, and zinc oxide doped with aluminum; resin particles coated with metals; and the like.
[0076] As a method for forming a resin layer on the surface of magnetic particles, for example, a wet method and a dry method can be cited. The wet method is a method using a solvent that dissolves or disperses the resin constituting the resin layer. On the other hand, the dry method is a method that does not use the above solvent.
[0077] As wet production methods, for example, there can be cited: an immersion method, in which the magnetic particles are immersed in a resin liquid for forming a resin layer for coating; a spray method, in which the resin liquid for forming a resin layer is sprayed onto the surface of the magnetic particles; a fluidized bed method, in which the magnetic particles are made to flow in a fluidized bed and the resin liquid for forming a resin layer is sprayed in this state; a kneading coater method, in which the magnetic particles and the resin liquid for forming a resin layer are mixed in a kneading coater and the solvent is removed; and the like.
[0078] The resin liquid for forming the resin layer used in the wet method is prepared by dissolving or dispersing the resin and other components in a solvent. The solvent is not particularly limited as long as it can dissolve or disperse the resin, and examples thereof include aromatic hydrocarbons such as toluene and xylene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; and the like.
[0079] As a dry method, for example, a mixture of magnetic particles and a resin for forming a resin layer is heated in a dry state to form a resin layer. Specifically, for example, magnetic particles and a resin for forming a resin layer are mixed in a gas phase and heated to melt to form a resin layer.
[0080] Next, a dry coating method will be described as an embodiment of the dry method.
[0081] The dry coating method is a method in which resin particles are attached to the surface of the magnetic particles to be coated, and then a mechanical impact force is applied to melt or soften the resin particles attached to the surface of the magnetic particles to form a resin layer. Specifically, a mixture containing magnetic particles and resin particles (and inorganic particles contained in the resin layer if necessary) is put into a high-speed stirring mixer that can generate mechanical impact force, and high-speed stirring is performed under non-heating or heating to repeatedly apply impact force to the mixture. As the stirring force, for example, wind force can be cited.
[0082] When heating is performed during high-speed stirring, the temperature range is preferably 80° C. to 130° C. The wind speed during high-speed stirring is preferably 10 m / s or more during heating, and preferably 5 m / s or less from the perspective of suppressing the aggregation of the resin-coated carriers during cooling. The time for applying the impact force is preferably in the range of 20 minutes to 60 minutes.
[0083] Preferably, when or after the resin-coated carrier is manufactured by the above method, a portion of the resin layer is peeled off by applying mechanical stress to the resin-coated carrier, thereby exposing the magnetic particles. For example, the wind speed during cooling is set to a high speed to generate a shear force, thereby exposing a portion of the resin layer. For example, by extending the time for applying the impact force (for example, more than 90 minutes), the resin located on the surface of the convex portion of the resin-coated carrier moves to the concave portion, thereby exposing the magnetic particles on the convex portion. For example, the manufactured resin-coated carrier is stirred using a high-speed paddle mixer (タービュラー), a ball mill, a vibration grinder, etc., thereby exposing a portion of the resin layer.
[0084] The thickness of the resin layer is preferably 0.1 μm to 10 μm, and more preferably 0.3 μm to 5 μm.
[0085] The exposed ratio of the magnetic particles on the surface of the resin-coated carrier is preferably 1% to 20%, more preferably 2% to 10%, and even more preferably 3% to 8%.
[0086] The exposed ratio of the magnetic particles on the surface of the resin-coated carrier is determined by X-ray photoelectron spectroscopy (XPS) according to the following method.
[0087] A resin-coated carrier as a target and magnetic particles obtained by removing the resin layer from the resin-coated carrier as a target are prepared. As a method for removing the resin layer from the resin-coated carrier, for example, a method of removing the resin layer by dissolving the resin component with an organic solvent, a method of removing the resin layer by heating at about 800°C to eliminate the resin component, etc. The resin-coated carrier and the magnetic particles obtained by removing the resin layer are respectively used as measurement samples, and Fe (atomic %) is quantified by XPS, and (Fe of the resin-coated carrier) ÷ (Fe of the magnetic particles) × 100 is calculated, and this is taken as the exposure ratio (%) of the magnetic particles.
[0088] The exposed ratio of the magnetic particles in the resin-coated carrier can be controlled by the amount of the resin used to form the resin layer. The larger the amount of the resin relative to the amount of the magnetic particles, the smaller the exposed ratio.
[0089] The volume average particle size of the resin-coated carrier is preferably 10 μm to 120 μm, more preferably 20 μm to 100 μm, and even more preferably 30 μm to 80 μm.
[0090] The mixing ratio (mass ratio) of the resin-coated carrier and the toner particles in the developer of the present embodiment is preferably resin-coated carrier:toner particles=100:1 to 100:30, and more preferably 100:3 to 100:20.
[0091] [Layered compound particles]
[0092] The layered compound particles are particles of a compound having a layered structure. Examples of the layered compound particles containing nitrogen atoms include melamine cyanurate particles and boron nitride particles.
[0093] From the perspective of suppressing the occurrence of beads carry over, the volume average particle size of the layered structure compound particles is preferably 0.1 μm or more and 20 μm or less. It is speculated that when the volume average particle size of the layered structure compound particles is 20 μm or less, they are easily attached to the exposed portion of the magnetic particles on the surface of the resin-coated carrier. It is speculated that when the volume average particle size of the layered structure compound particles is 0.1 μm or more, after being attached to the exposed portion of the magnetic particles on the surface of the resin-coated carrier, the exposed portion is easily covered.
[0094] From the above viewpoints, the volume average particle size of the layered structure compound particles is more preferably 0.3 μm to 10 μm, further preferably 1 μm to 8 μm, and still more preferably 2 μm to 6 μm.
[0095] The volume average particle size of the layered structure compound particles can be controlled by pulverization, classification, or a combination of pulverization and classification.
[0096] The ratio Da / Db of the volume average particle size Da of the layered structure compound particles to the volume average particle size Db of the resin-coated carrier is preferably 0.02 to 0.8, more preferably 0.03 to 0.7, and further preferably 0.04 to 0.6.
[0097] The volume average particle size of the layered structure compound is determined by the following measurement method.
[0098] First, the layered structure compound particles are separated from the developer. There is no limitation on the method for separating the layered structure compound particles from the developer. For example, the developer is dispersed in water containing a surfactant and ultrasonic waves are applied to the obtained dispersion. The dispersion is then centrifuged at high speed to centrifuge the developer particles, the layered structure compound particles, and other external additives according to their specific gravity. The fraction containing the layered structure compound particles is extracted and dried to obtain the layered structure compound particles.
[0099] Next, the layered structure compound particles are added to an electrolyte aqueous solution (e.g., an isotonic aqueous solution), and ultrasonic waves are applied for more than 30 seconds to disperse them. The dispersion is used as a sample, and the particle size is measured using a laser diffraction scattering particle size distribution measuring device (e.g., Microtrac BEL, Microtrac MT3000II). At least 3,000 layered structure compound particles are measured, and the particle size of 50% accumulated from the small diameter side in the volume-based particle size distribution is taken as the volume average particle size.
[0100] From the perspective of suppressing the occurrence of beads carry over, the content of the layered structure compound particles is preferably 0.01 parts by mass or more relative to 100 parts by mass of the toner particles, and from the perspective of suppressing the occurrence of ink starvation, the content of the layered structure compound particles is preferably 0.50 parts by mass or less relative to 100 parts by mass of the toner particles.
[0101] From the above viewpoints, the content of the layered structure compound particles is more preferably 0.01 to 0.30 parts by mass, further preferably 0.03 to 0.30 parts by mass, and still more preferably 0.05 to 0.15 parts by mass, based on 100 parts by mass of the toner particles.
[0102] [Toner particles]
[0103] The toner particles contain, for example, a binder resin and, if necessary, a colorant, a release agent, and other additives.
[0104] - Adhesive resin -
[0105] Examples of the adhesive resin include vinyl resins formed by homopolymers of the following monomers or copolymers of two or more of these monomers: styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), and the like.
[0106] Examples of the adhesive resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosins, mixtures thereof with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these resins.
[0107] These adhesive resins may be used alone or in combination of two or more.
[0108] As the adhesive resin, a polyester resin is suitable.
[0109] As the polyester resin, for example, a known amorphous polyester resin can be cited. Among the polyester resins, an amorphous polyester resin and a crystalline polyester resin can be used together. Among them, it is preferable to use the crystalline polyester resin in an amount of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) relative to the total binder resin.
[0110] The "crystallinity" of a resin means that there is no step-like change in endothermic value in differential scanning calorimetry (DSC) and that the resin has a clear endothermic peak. Specifically, the half-width of the endothermic peak when measured at a heating rate of 10 (°C / min) is within 10°C.
[0111] On the other hand, the "amorphous" nature of a resin means that the half-peak width is larger than 10°C, the endothermic value shows a step-like change, or a clear endothermic peak is not confirmed.
[0112] Amorphous polyester resin
[0113] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the non-crystalline polyester resin, a commercially available product or a synthetic product may be used.
[0114] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), and their anhydrides or their lower (e.g., carbon number 1 to 5) alkyl esters. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.
[0115] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of the trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0116] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0117] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0118] As the polyol, a diol may be used in combination with a trivalent or higher polyol having a cross-linked structure or a branched structure. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.
[0119] The polyols may be used alone or in combination of two or more.
[0120] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C to 80°C, and more preferably 50°C to 65°C.
[0121] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for measuring glass transition temperature of JIS K7121:1987 "Method for measuring transition temperature of plastics".
[0122] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 to 1,000,000, and more preferably 7,000 to 500,000.
[0123] The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less.
[0124] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0125] The weight average molecular weight and the number average molecular weight were measured by gel permeation chromatography (GPC). In the molecular weight measurement using GPC, a Tosoh GPC HLC-8120GPC was used as a measuring device, a Tosoh column TSKgel SuperHM-M (15 cm) was used, and THF solvent was used. The weight average molecular weight and the number average molecular weight were calculated based on the measurement results using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample.
[0126] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water or alcohol generated during condensation.
[0127] When the raw material monomers are insoluble or compatible at the reaction temperature, a high boiling point solvent can be added as a dissolving aid to dissolve them. In this case, the polycondensation reaction is carried out while the dissolving aid is distilled off. When there are monomers with poor compatibility in the copolymerization reaction, the monomers with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomers, and then polycondensed with the main component.
[0128] Crystalline polyester resin
[0129] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.
[0130] Here, in order to make the crystalline polyester resin easily form a crystal structure, a polycondensate obtained by using a straight-chain aliphatic polymerizable monomer is preferred over a polycondensate obtained by using a polymerizable monomer having an aromatic ring.
[0131] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0132] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a cross-linked structure or a branched structure may be used in combination. Examples of trivalent carboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0133] As the polycarboxylic acid, these dicarboxylic acids may be used in combination with a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond.
[0134] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0135] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosandiol. Among these, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.
[0136] Among the polyols, diols may be used in combination with trivalent or higher alcohols having a cross-linked structure or a branched structure. Examples of the trivalent or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0137] The polyols may be used alone or in combination of two or more.
[0138] Here, the content of the aliphatic diol in the polyol may be 80 mol % or more, and preferably 90 mol % or more.
[0139] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.
[0140] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K7121:1987 “Method for measuring transition temperatures of plastics”.
[0141] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0142] The crystalline polyester resin can be obtained, for example, by a known production method similar to the amorphous polyester.
[0143] The content of the binder resin is preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and further preferably 60% by mass to 85% by mass, based on the entire toner particles.
[0144] -Colorants-
[0145] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Vochug red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, ultramarine blue, oil-soluble blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; and dyes such as acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, nigrosine, polymethine, triphenylmethane, diphenylmethane and thiazole.
[0146] The coloring agent may be used alone or in combination of two or more.
[0147] The colorant may be a colorant that has been subjected to a surface treatment as required, or may be used in combination with a dispersant. In addition, two or more colorants may be used in combination.
[0148] The content of the colorant is preferably from 1 mass % to 30 mass % both inclusive, and more preferably from 3 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0149] - Anti-sticking agent -
[0150] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral / petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.
[0151] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.
[0152] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K7121:1987 “Method for measuring transition temperatures of plastics”.
[0153] The content of the release agent is preferably from 1 mass % to 20 mass % both inclusive, and more preferably from 5 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0154] -Other additives-
[0155] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives may be contained in the toner particles as internal additives.
[0156] -Characteristics of toner particles, etc.-
[0157] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.
[0158] The toner particles of a core-shell structure may be composed of, for example, a core portion including a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer including a binder resin.
[0159] The volume average particle diameter (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0160] The volume average particle size (D50v) of the toner particles is measured using Coulter Multisizer II (manufactured by Beckman Coulter) and ISOTON-II (manufactured by Beckman Coulter) for the electrolyte.
[0161] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and the solution is added to 100 ml to 150 ml of the electrolyte.
[0162] The electrolyte in which the sample is suspended is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with a particle size of 2 μm or more and 60 μm or less is measured using a Coulter Multisizer II with a hole of 100 μm in diameter. The number of particles sampled is 50,000. The volume-based particle size distribution is drawn from the small diameter side, and the particle size at the cumulative 50% point is taken as the volume average particle size D50v.
[0163] The average circularity of the toner particles is preferably from 0.94 to 1.00, and more preferably from 0.95 to 0.98.
[0164] The average circularity of the toner particles is determined by (equivalent circular circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.
[0165] First, the toner particles to be measured are collected by suction and formed into a flat flow, and the particles are momentarily strobed to obtain a particle image as a still image, and the particle image is analyzed by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.
[0166] When the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.
[0167] -Method for producing toner particles-
[0168] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation and coalescence methods, suspension polymerization methods, dissolution and suspension methods, etc.). These methods are not particularly limited, and known methods are used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.
[0169] Specifically, for example, in the case of manufacturing toner particles by an agglomeration and coalescence method, the toner particles are manufactured through the following steps: a step of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed (resin particle dispersion preparation step); a step of agglomerating resin particles (and other particles if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions if necessary) to form agglomerated particles (agglomerated particle formation step); and a step of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to fuse / merge (fusion / unity) the agglomerated particles to form toner particles (fusion / merging step).
[0170] The details of each step are described below.
[0171] In the following description, a method for obtaining toner particles containing a colorant and a release agent is described, but the colorant and the release agent are additives used as necessary. Of course, other additives besides the colorant and the release agent may also be used.
[0172] - Resin particle dispersion preparation step -
[0173] A resin particle dispersion in which resin particles as a binder resin are dispersed is prepared, and at the same time, for example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0174] The resin particle dispersion is prepared, for example, by dispersing the resin particles in a dispersion medium using a surfactant.
[0175] Examples of the dispersion medium used for the resin particle dispersion include aqueous media.
[0176] Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These media may be used alone or in combination of two or more.
[0177] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols; and the like. Among these, anionic surfactants and cationic surfactants can be particularly mentioned. Nonionic surfactants can be used in combination with anionic surfactants or cationic surfactants.
[0178] The surfactant may be used alone or in combination of two or more.
[0179] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, for example, a common dispersion method using a rotary shearing type homogenizer or a ball mill, sand mill, bead mill, etc. with a medium can be cited. In addition, depending on the type of resin particles, the resin particles can also be dispersed in the dispersion medium using a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (O phase) for neutralization, and then an aqueous medium (W phase) is added to thereby invert the phase from W / O to O / W, so that the resin is dispersed in the aqueous medium in a particle form.
[0180] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.
[0181] The volume average particle size of the resin particles is determined by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.). A cumulative distribution is plotted for the volume from the small particle size side with respect to the divided particle size range (segment), and the particle size at the cumulative 50% point with respect to all particles is measured, and this particle size is taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions is measured in the same manner.
[0182] The content of the resin particles contained in the resin particle dispersion is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 40% by mass or less.
[0183] For example, a colorant particle dispersion and a release agent particle dispersion are prepared in the same manner as the resin particle dispersion. That is, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0184] - Agglomerated Particle Formation Step-
[0185] Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed.
[0186] Thereafter, the resin particles, the colorant particles, and the release agent particles are heterogeneously aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0187] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to acidity (for example, pH 2 to 5), a dispersion stabilizer is added as needed, and then heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles is not less than -30°C and not more than -10°C), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.
[0188] In the aggregated particle forming step, for example, a coagulant may be added at room temperature (e.g., 25° C.) while the mixed dispersion is stirred using a rotary shearing homogenizer, the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 to 5), a dispersion stabilizer may be added as needed, and then the mixture may be heated.
[0189] Examples of the coagulant include surfactants having opposite polarity to the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of surfactant used is reduced and the charging characteristics are improved.
[0190] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As the additive, a chelating agent is preferably used.
[0191] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and the like.
[0192] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and the like.
[0193] The amount of the chelating agent added is preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.
[0194] - Fusion / Merge Steps-
[0195] Next, the aggregated particle dispersion containing the dispersed aggregated particles is heated to, for example, a temperature higher than the glass transition temperature of the resin particles (eg, 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse / combine the aggregated particles to form toner particles.
[0196] Through the above steps, toner particles are obtained.
[0197] After obtaining a dispersion of aggregated particles dispersed therein, toner particles can be manufactured by the following steps: further mixing the dispersion of aggregated particles with a dispersion of resin particles dispersed therein, agglomerating the resin particles so as to further adhere to the surfaces of the aggregated particles to form second aggregated particles; and heating the second dispersion of aggregated particles in which the second aggregated particles are dispersed to fuse / merge the second aggregated particles to form toner particles with a core-shell structure.
[0198] After the fusion / merging step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles. Regarding the washing step, from the perspective of charging performance, replacement washing using ion exchange water can be fully implemented. Regarding the solid-liquid separation step, from the perspective of productivity, suction filtration, pressure filtration, etc. can be implemented. Regarding the drying step, from the perspective of productivity, freeze drying, airflow drying, fluidized bed drying, vibration fluidized bed drying, etc. can be implemented.
[0199] Thereafter, for example, an external additive is added to the obtained dry toner particles and mixed, thereby producing the developer of the present embodiment. Mixing can be performed using, for example, a V-type blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, coarse particles of the toner can be removed using a vibration sieving machine, a wind sieving machine, etc. as needed.
[0200] -External Additives-
[0201] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.
[0202] The surface of the inorganic particles as an external additive can be subjected to a hydrophobic treatment. The hydrophobic treatment is carried out by, for example, immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.
[0203] The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.
[0204] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate, melamine resin, and other resin particles), detergent active agents (metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies).
[0205] The amount of the external additive added is preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.
[0206] <Image Forming Apparatus, Image Forming Method>
[0207] The image forming device of the present embodiment comprises: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holder; a developing mechanism for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium. In addition, as the electrostatic image developer, the electrostatic image developer of the present embodiment is applied.
[0208] The image forming device of the present embodiment is used to implement an image forming method (the image forming method of the present embodiment) having the following steps: a charging step of charging the surface of the image retaining body; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image retaining body; a developing step of developing the electrostatic image formed on the surface of the image retaining body into a toner image using the electrostatic image developer of the present embodiment; a transfer step of transferring the toner image formed on the surface of the image retaining body to the surface of the recording medium; and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0209] The structure of the image forming device of the present embodiment is applicable to the following well-known image forming devices: a device using a direct transfer method for directly transferring a toner image formed on the surface of an image holder to a recording medium; a device using an intermediate transfer method for transferring a toner image formed on the surface of an image holder to the surface of an intermediate transfer body for the first time, and transferring the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium for a second time; a device having a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred and before charging; a device having a de-staticizing mechanism for irradiating the surface of the image holder with de-staticizing light for de-staticizing after the toner image is transferred and before charging; and the like.
[0210] When the image forming device of the present embodiment is an intermediate transfer type device, the transfer mechanism used is, for example, a structure having the following components: an intermediate transfer body that transfers the colorant image to a surface; a primary transfer mechanism that transfers the colorant image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time; and a secondary transfer mechanism that transfers the colorant image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time.
[0211] In the image forming apparatus of this embodiment, for example, the part including the developing mechanism may be a cartridge structure (process cartridge) that is detachably mounted in the image forming apparatus. As the process cartridge, for example, a process cartridge that stores the electrostatic image developer of this embodiment and includes the developing mechanism is preferably used.
[0212] An example of the image forming apparatus according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the other descriptions are omitted.
[0213] Figure 1 2 is a diagram schematically showing the structure of the image forming apparatus according to the present embodiment.
[0214] Figure 1 The image forming apparatus shown in the figure comprises: first to fourth image forming units 10Y, 10M, 10C, 10K (image forming mechanism) of an electrophotographic method for outputting images of yellow (Y), magenta (M), cyan (C), and black (K) colors based on color separation image data. These image forming units (hereinafter sometimes referred to as "units") 10Y, 10M, 10C, 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. These units 10Y, 10M, 10C, 10K may be process cartridges that are detachable from the image forming apparatus.
[0215] Above each unit 10Y, 10M, 10C, 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 is provided to extend through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a supporting roller 24 so as to travel in a direction from the first unit 10Y toward the fourth unit 10K. The supporting roller 24 is applied with a force in a direction away from the driving roller 22 by a spring (not shown) or the like, and tension is applied to the intermediate transfer belt 20 wound around the two. An intermediate transfer body cleaning device 30 is provided on the image holding body side of the intermediate transfer belt 20, which is opposed to the driving roller 22.
[0216] The yellow, magenta, cyan and black toners stored in the toner cartridges 8Y, 8M, 8C and 8K are supplied to the developing devices (an example of developing mechanisms) 4Y, 4M, 4C and 4K of the respective units 10Y, 10M, 10C and 10K.
[0217] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y disposed on the upstream side in the traveling direction of the intermediate transfer belt and forming a yellow image will be described as a representative.
[0218] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging mechanism) 2Y that charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming mechanism) 3 that forms an electrostatic image by exposing the charged surface using a laser beam 3Y based on a color separation image signal; a developing device (an example of a developing mechanism) 4Y that supplies the charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer mechanism) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning unit) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.
[0219] The primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is provided at a position facing the photosensitive body 1Y. The primary transfer rollers 5Y, 5M, 5C, and 5K of each unit are connected to bias power supplies (not shown) for applying primary transfer bias. Each bias power supply changes the value of the transfer bias applied to each primary transfer roller under the control of a control unit (not shown).
[0220] Next, the operation of forming a yellow image in the first unit 10Y will be described.
[0221] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.
[0222] The photoreceptor 1Y has a conductivity (e.g., a volume resistivity of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ωcm or less. The photosensitive layer generally has a high resistance (resistance of a common resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when the laser beam is irradiated. Therefore, according to the yellow image data sent from the control unit (not shown), the laser beam 3Y is irradiated from the exposure device 3 to the surface of the charged photoreceptor 1Y. As a result, an electrostatic image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0223] The electrostatic image is an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image. The negative latent image is formed as follows: the resistivity of the irradiated portion of the photosensitive layer is reduced by using the laser beam 3Y, so that the charged charge on the surface of the photoreceptor 1Y flows; on the other hand, the charge of the portion not irradiated with the laser beam 3Y remains, thereby forming the negative latent image.
[0224] The electrostatic image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y runs. At the development position, the electrostatic image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and visualized.
[0225] The developing device 4Y stores an electrostatic image developer containing, for example, at least a yellow toner and a carrier. The yellow toner is frictionally charged by being stirred inside the developing device 4Y, and is held on a developer roller (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge charged on the photoreceptor 1Y. The surface of the photoreceptor 1Y is then passed through the developing device 4Y, whereby the yellow toner is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y that has been de-charged, and the latent image is developed using the yellow toner. The photoreceptor 1Y on which the yellow toner image is formed continues to run at a preset speed, and the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.
[0226] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and the electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, so that the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control section (not shown) in the first unit 10Y.
[0227] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.
[0228] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled in accordance with the first unit.
[0229] In this way, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is transported sequentially through the second to fourth units 10M, 10C, and 10K, and the toner images of the respective colors are multiply transferred in a superimposed manner.
[0230] The intermediate transfer belt 20 to which the toner images of four colors have been multi-transferred by the first to fourth units arrives at the secondary transfer section, which is composed of the intermediate transfer belt 20, the support roller 24 in contact with the inner surface of the intermediate transfer belt, and the secondary transfer roller (an example of the secondary transfer mechanism) 26 arranged on the image holding surface side of the intermediate transfer belt 20. On the other hand, the recording paper (an example of the recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 at a preset timing by the feeding member, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same (-) polarity as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. The secondary transfer bias at this time is determined based on the resistance detected by the resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled.
[0231] Thereafter, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in a fixing device (an example of a fixing mechanism) 28 , and the toner image is fixed on the recording paper P to form a fixed image.
[0232] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include, in addition to the recording paper P, OHP transparent films, etc.
[0233] In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth. For example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, art paper for printing, etc. are preferably used.
[0234] The recording paper P on which the color image has been fixed is sent to the discharge portion, and a series of color image forming operations are completed.
[0235] <Processing cartridge>
[0236] The process cartridge of this embodiment is a process cartridge that is detachably mounted in an image forming apparatus and includes a developing mechanism that stores the electrostatic image developer of this embodiment and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer.
[0237] The process cartridge of this embodiment is not limited to the above-described configuration, and may include a developing mechanism and, if necessary, at least one of other mechanisms selected from an image holding member, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism.
[0238] An example of the process cartridge according to the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and the other descriptions are omitted.
[0239] Figure 2 It is a schematic structural diagram showing the process cartridge of this embodiment.
[0240] Figure 2 The processing box 200 shown is constructed by, for example, integrally combining and retaining a photosensitive body 107 (an example of an image holding body) and a charging roller 108 (an example of a charging mechanism) provided around the photosensitive body 107, a developing device 111 (an example of a developing mechanism), and a photosensitive body cleaning device 113 (an example of a cleaning mechanism) through a shell 117 having a mounting guide 116 and an opening 118 for exposure to form an ink cartridge.
[0241] Figure 2 In the figure, 109 denotes an exposure device (an example of an electrostatic image forming mechanism), 112 denotes a transfer device (an example of a transfer mechanism), 115 denotes a fixing device (an example of a fixing mechanism), and 300 denotes recording paper (an example of a recording medium).
[0242] [Example]
[0243] The embodiments of the present invention are described in detail below by way of examples, but the embodiments of the present invention are not limited to these examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.
[0244] <Production of Toner Particles>
[0245] [Preparation of amorphous polyester resin dispersion (A1)]
[0246] Ethylene glycol: 37 parts
[0247] Neopentyl glycol: 65 parts
[0248] 1,9-nonanediol: 32 parts
[0249] Terephthalic acid: 96 parts
[0250] The above materials were put into a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was uniformly stirred, 1.2 parts of dibutyltin oxide were added. The temperature was raised to 240°C over 6 hours while distilling off the generated water. Stirring was continued at 240°C for 4 hours to obtain an amorphous polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). The amorphous polyester resin was kept in a molten state and conveyed to an emulsifier (Cavitron CD1010, Eurotec) at a rate of 100 g per minute. Separately, the reagent ammonia water was diluted with ion exchange water and the obtained 0.37% concentration of dilute ammonia water was put into a tank, heated to 120°C by a heat exchanger, and conveyed to the emulsifier together with the amorphous polyester resin at a rate of 0.1 liter per minute. The emulsifier was operated at a rotor rotation speed of 60 Hz and a pressure of 5 kg / cm 2 The reaction mixture was operated under the conditions of , to obtain an amorphous polyester resin dispersion (A1) having a volume average particle size of 160 nm and a solid content of 20%.
[0251] [Preparation of Crystalline Polyester Resin Dispersion (C1)]
[0252] Sebacic acid: 81 parts
[0253] Hexanediol: 47 parts
[0254] The above materials were placed in a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was uniformly stirred, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while distilling off the generated water, and stirring was continued at 200°C for 4 hours. The reaction liquid was then cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C / under reduced pressure to obtain a crystalline polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).
[0255] Crystalline polyester resin (C1): 50 parts
[0256] Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Chemical Co., Ltd.): 2 parts
[0257] Ion exchange water: 200 parts
[0258] The above materials were heated to 120°C, fully dispersed with a homogenizer (ULTRA-TURRAXT50, IKA), and then dispersed with a pressure discharge homogenizer. After the volume average particle size reached 180 nm, the particles were recovered to obtain a crystalline polyester resin dispersion (C1) with a solid content of 20%.
[0259] [Preparation of Release Agent Particle Dispersion (W1)]
[0260] Solid paraffin wax (HNP-9 manufactured by Nippon Seiro Co., Ltd.): 100 parts
[0261] Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Chemical Co., Ltd.): 1 part
[0262] Ion exchange water: 350 parts
[0263] The above materials were mixed, heated to 100°C, dispersed using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), and then dispersed using a pressure-dispensing Gaulin homogenizer to obtain a dispersion of anti-adhesive particles having a volume average particle size of 200 nm. Ion-exchanged water was added to the anti-adhesive particle dispersion to adjust the solid content to 20%, thereby obtaining an anti-adhesive particle dispersion (W1).
[0264] [Preparation of Colorant Particle Dispersion (K1)]
[0265] Carbon black (Regal 330 manufactured by Cabot Corporation): 50 parts
[0266] Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Chemical Co., Ltd.): 5 parts
[0267] Ion exchange water: 195 parts
[0268] The above materials were mixed and dispersed at 240 MPa for 10 minutes using an Ultimaizer (manufactured by Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (K1) having a solid content of 20%.
[0269] [Preparation of Toner Particles]
[0270]
[0271] The above materials were placed in a round stainless steel flask, 0.1N nitric acid was added to adjust the pH to 3.5, and then an aqueous solution of polyaluminum chloride (manufactured by Oji Paper Co., Ltd., 30% powder) was added to dissolve 2 parts of polyaluminum chloride in 30 parts of ion exchange water. After dispersion at 30°C using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), it was heated to 45°C in a heating oil bath and maintained until the volume average particle size reached 4.9μm. Then, 60 parts of amorphous polyester resin dispersion (A1) were added and maintained for 30 minutes. Next, when the volume average particle size reached 5.2μm, 60 parts of amorphous polyester resin dispersion (A1) were further added and maintained for 30 minutes. Then, 20 parts of a 10% NTA (nitrilotriacetic acid) metal salt aqueous solution (Chelest70, manufactured by Chelest Co., Ltd.) were added, and a 1N sodium hydroxide aqueous solution was added to adjust the pH to 9.0. Then, 1 part of anionic surfactant (Tayca Power) was added, and the mixture was heated to 85° C. and maintained for 5 hours while continuing to stir. Then, the mixture was cooled to 20° C. at a rate of 20° C. / min. Then, the mixture was filtered, washed thoroughly with ion exchange water, and dried to obtain toner particles (1) having a volume average particle size of 5.7 μm and an average circularity of 0.971.
[0272] <Production of Layered Compound Particles>
[0273] [Production of melamine cyanurate granules]
[0274] Commercially available melamine cyanurate (MC-4500 manufactured by Nissan Chemical) was pulverized by a jet mill and classified to obtain melamine cyanurate particles (1) to (5). Table 1 shows the volume average particle size of melamine cyanurate particles (1) to (5). "MC" in Table 1 means melamine cyanurate.
[0275] [Preparation of Boron Nitride Particles]
[0276] Commercially available boron nitride particles (MARUKA product, AP-10S) were prepared. The volume average particle size was 2.4 μm. "BN" in Table 1 means boron nitride.
[0277] <Preparation of Resin-Coated Carrier>
[0278] [Preparation of resin-coated carrier (1)]
[0279] The raw materials were weighed according to MnO: 35 mol%, MgO: 14.5 mol%, Fe2O3: 50 mol% and SrO: 0.5 mol%, mixed with water, and crushed in a wet medium mill for 5 hours to obtain a slurry. The slurry was dried in a spray dryer to obtain spherical particles. After the particle size of the particles was adjusted, they were heated at 950°C for 2 hours and pre-fired. Stainless steel beads with a diameter of 0.3 cm were used to crush them in a wet ball mill for 1 hour, and zirconia beads with a diameter of 0.5 cm were further used to crush them for 4 hours. Polyvinyl alcohol as a binder was added in an amount of 0.8 mass % relative to the solid content, and then granulated and dried using a spray dryer, and the main firing was carried out by maintaining the temperature at 1350°C for 5 hours in an electric furnace. Then, the particle size was adjusted by crushing and classification, and low magnetic products were separated by magnetic separation to obtain ferrite particles (1). The volume average particle size of the ferrite particles (1) was 35 μm.
[0280] Cyclohexyl methacrylate was added to a 0.3 mass % sodium benzenesulfonate aqueous solution, potassium persulfate was added in an amount corresponding to 0.5 mass % of the total monomer amount, emulsion polymerization was performed, and drying was performed by spray drying to obtain a coating resin (1). The weight average molecular weight of the coating resin (1) was 400,000.
[0281] 100 parts by mass of ferrite particles (1) and 4.5 parts by mass of coating resin (1) were added to a high-speed stirring mixer equipped with horizontal stirring blades, and stirred at 22°C for 15 minutes under the condition that the circumferential speed of the horizontal rotating paddle was 8 m / s, and then stirred at 120°C for 50 minutes to form a resin layer on the surface of the ferrite particles (1). Fine powder and coarse powder were removed from the obtained crude resin-coated carrier by sharp jet classification to obtain a resin-coated carrier (1). The volume average particle size of the resin-coated carrier (1) was 36 μm.
[0282] [Preparation of resin-coated carrier (2)]
[0283] A resin-coated carrier (2) was obtained in the same manner as in the production of the resin-coated carrier (1), except that the amount of the coating resin (1) charged was changed to 4.8 parts by mass.
[0284] [Preparation of resin-coated carrier (3)]
[0285] A resin-coated carrier (3) was obtained in the same manner as in the production of the resin-coated carrier (1), except that the amount of the coating resin (1) charged was changed to 4.3 parts by mass.
[0286] [Preparation of resin-coated carrier (4)]
[0287] A resin-coated carrier (4) was obtained in the same manner as in the production of the resin-coated carrier (1), except that the amount of the coating resin (1) charged was changed to 3.7 parts by mass.
[0288] Table 1 shows the maximum height Ry of the roughness curve of each surface of the resin-coated carriers (1) to (4).
[0289] <Example 1>
[0290] 100 parts by mass of toner particles (1), 1.5 parts by mass of hydrophobic silica particles (RY50 manufactured by NIPPON AEROSIL Co., Ltd.) and 0.12 parts by mass of melamine cyanurate particles (1) were placed in a sample mill and mixed at 10,000 rpm for 30 seconds. The mixture was then sieved using a vibrating sieve with a mesh size of 45 μm to prepare a toner having a volume average particle size of 5.7 μm. The toner and carrier (1) were placed in a V mixer at a ratio of toner:carrier (1) = 5:100 (mass ratio) and stirred for 20 minutes to obtain a developer.
[0291] <Examples 2 to 12, Comparative Examples 1 to 2>
[0292] A toner and a developer were obtained in the same manner as in Example 1 except that the type or amount of the layered structure compound particles or the type of the resin-coated carrier was changed.
[0293] <Performance Evaluation>
[0294] [Beads carry over (BCO)]
[0295] As an image forming apparatus, an Iridesse Production Press manufactured by Fuji Xerox was prepared. Using this image forming apparatus, 50,000 images with an image density of 0.5% were output on A4-sized plain paper (manufactured by Fuji Xerox, C2 paper) without supplying a trickle carrier under an environment of 30°C and a relative humidity of 88%. Next, one full-surface halftone image was output on A3-sized plain paper (manufactured by Fuji Xerox, C2 paper). The number of carriers on the full-surface halftone image was counted and classified as follows.
[0296] G1: 0.
[0297] G2: 1 to 3.
[0298] G3: 4 to 6. Permissible range.
[0299] G4: 7 or more. This is not practically acceptable.
[0300] [Ink Hunger (STV)]
[0301] After the above-mentioned image formation, the image forming apparatus was transferred to an environment with a temperature of 10°C and a relative humidity of 15% and left overnight. Then, in an environment with a temperature of 10°C and a relative humidity of 15%, 100 sheets of A4-sized plain paper (manufactured by Fuji Xerox, C2 paper) were passed through the image forming apparatus, and then, without supplying a trickle carrier, 50,000 images with an image density of 50% were output on A4-sized plain paper (manufactured by Fuji Xerox, C2 paper). Then, one image for evaluating ink thirst was output on A4-sized plain paper (manufactured by Fuji Xerox, C2 paper). The images for evaluating ink thirst were visually observed and classified as follows.
[0302] G1: The image has no deviation (ずれ).
[0303] G2: The image is slightly deviated, but the difference is too small to be immediately determined.
[0304] G3: The image is slightly deviated. Within the tolerance range.
[0305] G4: The image is significantly deviated. This is not acceptable in practice.
[0306] [Table 1]
[0307]
Claims
1. An electrostatic image developer comprising: Toner particles; Melamine cyanurate granules; and A resin-coated carrier having magnetic particles and a resin layer coating the magnetic particles, The volume average particle size of the melamine cyanurate particles is 2 μm or more and 10 μm or less. The surface of the resin-coated carrier has a maximum height Ry of a roughness curve specified in JIS B0601:1994 of 0.01 μm or more and 0.20 μm or less.
2. The electrostatic image developer according to claim 1, wherein The surface of the resin-coated carrier has a maximum height Ry of a roughness curve specified in JIS B0601:1994 of 0.01 μm or more and 0.10 μm or less.
3. The electrostatic image developer according to claim 1 or claim 2, wherein The volume average particle size of the melamine cyanurate particles is 2 μm or more and 8 μm or less.
4. The electrostatic image developer according to claim 1 or claim 2, wherein The content of the melamine cyanurate particles is 0.01 parts by mass or more and 0.50 parts by mass or less relative to 100 parts by mass of the toner particles.
5. The electrostatic image developer according to claim 4, wherein The content of the melamine cyanurate particles is 0.01 parts by mass or more and 0.30 parts by mass or less relative to 100 parts by mass of the toner particles.
6. A process cartridge detachably mounted in an image forming apparatus, comprising a developing mechanism storing the electrostatic image developer according to any one of claims 1 to 5 and developing an electrostatic image formed on a surface of an image holding member into a toner image using the electrostatic image developer.
7. An image forming apparatus comprising: Image holding body; A charging mechanism for charging the surface of the image holding body; An electrostatic image forming mechanism for forming an electrostatic image on the charged surface of the image holding member; a developing mechanism storing the electrostatic image developer according to any one of claims 1 to 5, and developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer; A transfer mechanism for transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; as well as The fixing mechanism fixes the toner image transferred to the surface of the recording medium.
8. An image forming method comprising the following steps: A charging step of charging the surface of the image holding body; An electrostatic image forming step of forming an electrostatic image on the charged surface of the image holding member; a developing step of developing the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer according to any one of claims 1 to 5; a transfer step of transferring the toner image formed on the surface of the image holding body to the surface of the recording medium; as well as In the fixing step, the toner image transferred to the surface of the recording medium is fixed.
Citation Information
Patent Citations
Electrophotographic toner, cleaning device and image forming apparatus
JP2006317489A
Positively charged toner for developing electrostatically charged image
JP2009237274A
Electrostatic charge image developer, developer cartridge, process cartridge, imaging forming device and image forming method
CN107065468A
Electrostatic charge image developer, developer cartridge, process cartridge, image forming apparatus and image forming method
CN107065469A
Toner for electrostatic charge image development and image forming method
JP1996082948A